Leadership Disparities in State Governmental Public Health Workforce: Examining the Influence of Gender. Issue 1 (January 2020) - Chapple-McGruder, Theresa; Mendoza, Zipatly V.; Miles, Gandarvaka; Hilson, Renata; Wiltshire, Jacqueline; Wilder, Jocelyn; Heidari, Leila; Castrucci, Brian C.; Gould, Elizabeth
Abstract : Objective: To determine the extent to which gender disparities exist in either obtaining a leadership position or pay equity among those with leadership positions in state governmental public health agencies. Design: Utilizing the 2014 Public Health Workforce Interests and Needs Survey, a nationally representative cross-sectional study of state governmental public health agency employees, the characteristics of the state governmental public health agency leadership were described. We estimated the odds of being a manager or an executive leader and the odds of leaders earning greater than $95 000 annually for women compared with men using polytomous multinomial regression and logistic regression models, respectively. Setting and Participants: The Public Health Workforce Interests and Needs Survey was conducted via electronic survey at 37 state health departments. This study utilized only those respondents who listed their current position as a supervisory position (n = 3237). Main Outcome Measures: Leadership position and high-earning leadership were the 2 main outcome measures explored. Leadership position was defined as a 3-level ordinal variable: supervisor, manager, or executive leader. High-earning leadership was defined as a member of leadership earning $95 000 or greater. Results: Women accounted for 72.0% of the overall state governmental public health agency workforce and 67.1% of leadership positions. Women experienced lower odds (odds ratio = 0.55, 95% confidence interval: 0.39-0.78) of holding executive leadership positions than men and lower odds (odds ratio = 0.64, 95% confidence interval: 0.50-0.81) of earning an annual salary greater than $95 000. Conclusion: While women were represented in similar proportions in the general workforce as in leadership positions, gender disparities still existed within leadership positions. Increased effort is needed to ensure that opportunities exist for women in executive leadership positions and in pay equity. With public health's commitment to social justice and the benefits of diversity to an agency's policies and programs, it is important to ensure that women's voices are equally represented at all levels of leadership.